Effect of twin boundary on nanoimprint process of bicrystal Al thin film studied by molecular dynamics simulation - 谢月红 徐建刚 宋海洋 张云光 (Chinese physics B, 2015)
The effects of a twin boundary（TB） on the mechanical properties of two types of bicrystal Al thin films during the nanoimprint process are investigated by using molecular dynamics simulations.The results indicate that for the TB direction parallel to the imprinting direction,the yield stress reaches the maximum for the initial dislocation nucleation when the mould directly imprints to the TB,and the yield stress first decreases with the increase of the marker interval and then increases.However,for the TB direction perpendicular to the imprinting direction,the effect of the TB location to the imprinting forces is very small,and the yield stress is greater than that with the TB direction parallel to the imprinting direction.The results also demonstrate that the direction of the slip dislocations and the deformation of the thin film caused by spring-back are different due to various positions and directions of the TB.